Business Risk Management Ideology and Entrepreneurial Development of Students in Tertiary Institutions in Southwestern, Nigeria - Alli Noah GBenga (Journal of Technology Management and Business, 2024)
This study investigated the relationship between Business Risk Management (BRM) ideology and the entrepreneurial development of students in tertiary institutions within Southwestern Nigeria. A quantitative research design was employed, with data collected from a sample of 1918 students across five federal universities in the region. The research instrument was a structured questionnaire designed to gather information on risk identification, risk assessment and evaluation, risk mitigation and control strategies, entrepreneurial intentions, self-efficacy, and entrepreneurial behavior. The findings suggest a positive relationship between BRM ideology and the entrepreneurial development of students. Specifically, risk identification was found to significantly influence entrepreneurial intentions (p < 0.01) and self-efficacy (p < 0.05). Risk assessment and evaluation also demonstrated a significant positive impact on entrepreneurial intentions (p < 0.01), self-efficacy (p < 0.01), and entrepreneurial behavior (p < 0.05). Additionally, risk mitigation and control strategies were found to significantly contribute to entrepreneurial intentions (p < 0.01), self-efficacy (p < 0.01), and entrepreneurial behavior (p < 0.01). These findings highlight the importance of integrating BRM education into the curriculum of tertiary institutions in Southwestern Nigeria. By equipping students with the knowledge and skills to identify, assess, and mitigate potential risks, they are better prepared to navigate the challenges and uncertainties inherent in entrepreneurial ventures. This, in turn, can contribute to the growth of a vibrant and resilient entrepreneurial ecosystem in the region.